A broadband and tunable microwave absorption technology enabled by VGCFs/PDMS-EP shape memory composites. (15th April 2020) - Li, Xiang; Zhu, Yaofeng; Liu, Xuqing; Bin Xu, Ben; Ni, Qingqing
Highlights: Fabricated VGCFs/PDMS-EP shape memory composites used as microwave absorber. Achieved tunable and broadband microwave absorption by morphing the deformation of composites. The practical optimal minimal reflection loss reaches −55.7 dB at 2.0 mm. The effective absorption bandwidth reaches 9.8 GHz. The designed composites have widespread practical application. Abstract: A facile method for fabricating intelligent microwave absorber of vapor grown carbon fibers/Polydimethylsiloxane-epoxy resin shape memory composites (VGCFs/PDMS-SMEP) was proposed to deliver intelligently tunable and broadband microwave absorption performance. The maximal absorption intensity was regulated by varying the deformation of the composites driven by the superior shape memory property of SMEP, where practical the minimum reflection loss ( RLmin ) reaches −55.7 dB at 16.0 GHz with the thickness of 2.0 mm. The effective absorption bandwidth (EAB) reached 9.8 GHz, which covered the whole applied frequency range (8.2–18.0 GHz). The intelligent microwave absorption performance of the sample was attributed to robust conductive loss and dielectric loss enhanced by the dipole relaxations and multi-reflections. Thus, VGCFs/PDMS-SMEP composites serves as the key that really opens up opportunity for the application as flexible, shape memory and tunable high performance broadband microwave absorption absorber in frontiers such as wearable electronic devices, chips protection, stealth technology and information security.